PEMBIAYAAN PENDIDIKAN DALAM MENINGKATKAN MUTU PAI DI SD MUHAMMADIYAH NGESTIHARJO - Aisyatur Rasyidah; Rina Sarifah; Lustia Bekti; Djamaluddin Perawironegoro (Institut Agama Islam Al-Aziziyah Samalanga, 2022)
This study focuses on the management of school financing, and how schools improve the quality of education, especially for the quality of Islamic religious education through financing. Thus, this study aims as one of the strategies that can be applied by private education institutions in Indonesia. This study uses a qualitative method, with a case study of private school education financing, namely SD Muhammadiyah Ngestiharjo which is considered to be able to overcome the problem of financing private education. SD Muhammadiyah Ngestiharjo realizes a free education program by the government. Through this program, the management of education financing carried out by SD Muhammadiyah Ngestiharjo becomes disciplined through planning, implementation, supervision and accountability. This management is in accordance with the theory of financial management, namely through input-process-output. This activity is carried out so that financing in schools is realized and maintained so that the school's vision and mission can be achieved.